Primary productivity, biogeochemical buffers and factors controlling trophic status and ecosystem processes in Mediterranean coastal lagoons: a synthesis - Pierluigi Viaroli; Roberta Azzoni; Marco Bartoli; Gianmarco Giordani; Mariachiara Naldi; Daniele Nizzoli (Advances in Oceanography and Limnology, 2010)
Coastal lagoons are threatened by natural and anthropogenic factors that have been accelerated in the last decades, with detrimental effects on ecosystem and water quality, especially in sheltered systems. Eutrophication, macroalgal blooms, hypoxia and anoxia are among the main threats, which also impact on human activities, e.g. aquaculture and fishery. Study were performed from late 1980s to date in several Mediterranean lagoons, mainly in the Po river delta, in order to elucidate the main causes of such degenerative processes. Here we review (1) relationships between benthic vegetation and sediment biogeochemistry, with focus on factors determining eutrophication; (2) development of macroalgal blooms, with focus on causes and biogeochemical triggers of bloom onset; (3) perturbation of nitrogen cycling due to changes in benthic vegetation assemblages; (4) relationships between primary producers and benthic fauna, especially farmed species; (5) possible feedback loops among shellfish and primary producers.